Problems and Possibilities of Logging development in Indian Forestry - Maleta, B. P. (Indian Forester, 1982)
Scientific forestry In India is now 120 years old. Silvicultural principles have always been emphasised In our forest management plans while logging was a subject of little Interest to the professional foresters in the Forest Departments, as timber harvesting was the sole responsibility of private contractors. Good silviculture is necessary for regeneration and growth of the forests, but not sufficient condition for forestry sector to make an optimum contribution to national economy. Economical extraction and proper utilisation of timber resources is equally important in production forestry. Contractors' working is being gradually replaced by Forest Corporations in all the states. There is general awakening about the wastage of timber resources due to backward logging methods. Logging operations can be bettcr organised in Government sector and there is better scope for larger and panned investment for economical returns and faster development in logging practices in the country. There are problems. Forestry operation including logging, are in the hands of unskilled, un-organised and casual labour force, Conventional methods and primitive tools have been traditionally used in felling, convension and transport of timber which are western), time consuming, unsafe and hard for the workers. The forest worker has low productivity due to bad design of tools, poor maintenance and lack of training. Annual felling coupes are small and scattered. Logging planning based on proper data and marked intelligence is lacking. In absence of rational and personnel policy there is generally shortage of trained. organisational structure of departments and corporations is bureaucratic, less flexible and powers are centralised. Indigenous development of logging tools and equipments have saffered for want of co-ordination and inter-action between research bodies, users and manufactnrNs. The problems are not without possibilities of solution. Logging can be bettrr coordinated with silvicultural needs of the forests. Labour force can be organised, their efficiency can be improved by regular training, improving the methods and tools and by providing beller safety provisions. Some definite action programme to accelerate logging development process have been identified and discussed in this paper.